2019
DOI: 10.36227/techrxiv.11344931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stiffness Enhancement of a Superconducting Magnetic Bearing Using Shaped YBCO Bulks

Abstract: High-speed superconducting motors and generators stand to benefit from superconductor magnetic levitation bearings if their stiffness characteristics can be improved. Here we investigate a novel thrust bearing geometry, comprising a conical frustum shaped permanent magnet and matching superconducting toroid and puck assembly, aimed at producing high stiffness coupled with high levitation force. To this end, we have constructed a bearing test rig enabling measurements of the levitation force and stiffness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…For θ below about 25 • the curves develop an increasingly convex shape, with the 10 • curve possessing a maximum near z = 6 mm. A similar bell-curve shape was seen previously in our experiments [12] with a frustum/recess angle of 14 • . It stems from the average z-component of the field normally incident on the side walls of the recess changing sign as it the magnet is lowered into the recess.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For θ below about 25 • the curves develop an increasingly convex shape, with the 10 • curve possessing a maximum near z = 6 mm. A similar bell-curve shape was seen previously in our experiments [12] with a frustum/recess angle of 14 • . It stems from the average z-component of the field normally incident on the side walls of the recess changing sign as it the magnet is lowered into the recess.…”
Section: Resultssupporting
confidence: 89%
“…Recently, we showed that a levitation bearing based on a conical frustum shaped magnet recessed inside a superconducting bulk provides improved levitation force and lateral stiffness compared to a typical cylindrical magnet and superconductor arrangement [12]. In this follow-on work, we investigate the angle-dependence of the frustum/recess on levitation force, using previously benchmarked H-formulation models, to identify the optimal configuration for this design.…”
Section: Introductionmentioning
confidence: 99%
“…For θ below about 25 • the curves develop an increasingly convex shape, with the 10 • curve possessing a maximum near z = 6 mm. A similar bellcurve shape was seen previously in our experiments [12] with a frustum/recess angle of 14 • . It stems from the average zcomponent of the field normally incident on the side walls of the recess changing sign as it the magnet is lowered into the recess.…”
Section: Resultssupporting
confidence: 89%
“…Based on our experiments on YBCO high-temperature superconductor bulks [12] the critical current density was set to J c = 21 × 10 8 A/m 2 at the electric field criterion E c = 10 −4 V/m, and the n-value was set to 21. For simplicity a fieldindependent and spatially homogeneous J c was assumed.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation